Spray-Coated Melanin/PEDOT:PSS Films for Sustainable Organic Electrochemical Transistors. - Nozella, Natan L [UNESP]; Nogueira, Gabriel L [UNESP]; Paulin, João V [UNESP]; de Oliveira, Rafael F; Graeff, Carlos F O [UNESP] (MyJove, 2025)
A simple and scalable protocol for the fabrication of Melanin/PEDOT:PSS organic electrochemical transistors (OECTs) via spray coating is presented. The method includes melanin synthesis, blending with poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) PEDOT:PSS at different mass ratios (0, 10, 30, and 50 wt%, named Pure PEDOT:PSS, 10Mel, 30Mel, and 50Mel, respectively), and deposition onto gold-patterned substrates using a 3D printer-adapted spray-coating system. Electrical characterization is performed using a top-gate Ag/AgCl electrode in 100 mM NaCl aqueous electrolyte, with output and transfer curves recorded. Addition of 10 wt% melanin increases the normalized transconductance by approximately 2x compared to pristine PEDOT:PSS, while maintaining a high ON/OFF current ratio (>100). Threshold voltage shifts toward more negative potential, reflecting dedoping effects and the influence of melanin on device operation. Film morphology and thickness were systematically evaluated, providing insights into reproducibility across different compositions. This protocol enables the production of sustainable, high-performance OECTs for bioelectronic applications such as sensors, memory devices, and neuromorphic-inspired systems.